Risk of subarachnoid haemorrhage in people admitted to hospital with selected immune-mediated diseases: record-linkage studies. - Ramagopalan, S; Pakpoor, J; Seminog, O; Goldacre, R; Graham, L; Goldacre, M (BioMed Central, 2013)
BACKGROUND: Subarachnoid hemorrhage (SAH) is a devastating cause of stroke, occurring in relatively young people. It has been suggested that some immune-mediated diseases may be associated with an increased risk of SAH. METHODS: We analysed a database of linked statistical records of hospital admissions and death certificates for the whole of England (1999-2011). Rate ratios for SAH were determined, comparing immune-mediated disease cohorts with comparison cohorts. RESULTS: There were significantly elevated risks of SAH after hospital admission for the following individual immune-mediated diseases: Addison's disease, ankylosing spondylitis, autoimmune haemolytic anaemia, Crohn's disease, diabetes mellitus, idiopathic thrombocytopenia purpura, myxoedema, pernicious anaemia, primary biliary cirrhosis, psoriasis, rheumatoid arthritis, scleroderma, Sjogren's syndrome, SLE and thyrotoxicosis. Elevated risks that were greater than 2-fold were found for Addison's disease (rate ratio (RR) = 2.01, 95% confidence interval 1.3-2.97), idiopathic thrombocytopenia purpura (RR = 2.42, 1.86-3.11), primary biliary cirrhosis (RR = 2.21, 1.43-3.16) and SLE (RR = 3.76, 3.08-4.55). CONCLUSIONS: Our findings strongly support the suggestion that patients with some immune-mediated diseases have an increased risk of SAH. Further studies of the mechanisms behind this association are warranted.